Sequential Condensation and Hydrodeoxygenation Reaction of Furfural-Acetone Adduct over Mix Catalysts Ni/SiO2 and Cu/SiO2 in Water - Siti Mariyah Ulfa; Rizka Fauzia Ohorella; Caterina Widya Astutik (Universitas Gadjah Mada, 2018)
Sequential condensation and hydrodeoxygenation reaction were perform using autoclave batch reactor in the presence of water as a solvent. The condensation of furfural and acetone was performed using MgO catalyst followed by hydrodeoxygenation using mix catalyst Ni/SiO2 and Cu/SiO2. The catalyst was prepared by wet-impregnation method and analyzed by XRD, SEM-EDX as well as BET surface. Condensation of furfural and acetone in 1:2 mol ratio was carried out by reflux gave 4-(2-furyl)-3-buten-2-one and 1,5-bis-(2-furanyl)-1,4-pentadien-3-one. The condensation product was then subjected for hydrodeoxygenation using batch reactor, catalyzed by mixed Ni/SiO2 and Cu/SiO2 at 150 and 180 °C for 2 h. The product identified as alkane derivatives with the conversion at 38.83 and 50.35%, respectively. The selectivity of hydrocarbon is 61.39% at 150 °C and 16.55% at 180 °C. Increasing the reaction temperature to 200 °C did not give any products except the recovery of the precursor. It showed that higher temperature enhanced the catalyst activity but the selectivity is controlled by low reaction temperature.